Guaranteed convergence control for consensus of mobile sensor networks with dynamical topologies. (November 2016) - Li, Xiangshun; Lei, Cheng; Dong, Lijing; Nguang, Sing-Kiong
Mobile sensors need to reach consensus in many applications such as unmanned vehicles, multi-agent systems and environmental monitoring. In these scenarios, it is very important to reduce the power consumption as well as make sensors reach consensus as fast as possible. In this article, we propose a novel guaranteed convergence control algorithm to switch topologies of mobile sensors so that we can reduce power consumption in the sensor network and make the mobile sensors reach consensus with guaranteed convergence as well. The topology graphs over the mobile sensors are unconnected, directed, dynamical and switched periodically at any moment, while the joint graphs of dynamical topologies are connected in a bounded time period. The guaranteed convergence rate of consensus is derived on a method based on the variable decomposition. Some illustrative examples are provided to demonstrate the validity and effectiveness of the results.